Penambahan Tepung Labu Kuning Untuk Meningkatkan kecerahan Warna dan Pertumbuhan Ikan Cupang (Betta splendens) - Ratu Peo, Lusia Evatrita; Kusuma, Pungky Slamet Wisnu (Universitas PGRI Adi Buana Surabaya, 2023)
Betta fish is one type of ornamental fish with unique characteristics, namely having an attractive color, to increase the intensity of the color, Betta fish need to be added color pigments and beta-carotene derived from nature in their feed. Yellow pumpkin is known as a fruit and vegetable that contains carotenoids, especially β-carotene. This study aims to determine the effect of adding yellow pumpkin flour in commercial feed on increasing color brightness and growth of Betta fish. Complete Randomized Design (RAL) with 5 treatments and 5 repeats namely P0 (control), P1 (2.5%), P2 (5%), P3 (7.5%), and P4 (10%) for 3 months. The results showed that the P2 treatment produced significant color brightness (P<0.05) compared to control. Betta fish length growth was not significant (P>0.05). The weight growth of Betta fish treated with P3 was significant (P<0.05) compared to the control. The addition of pumpkin flour in commercial feed has been proven to increase color brightness and weight growth in betta fish. Keywords: Betta Fish; Pumpkin flour; Color brightness and growth.